2020
DOI: 10.1111/ger.12472
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an oral health education programme for older adults using a workbook

Abstract: Rise in the ageing population has placed significant importance on oral health care for older adults. Moreover, the emerging geriatric dentistry industry focuses on encouraging oral health care for this population, 1 as well as maintenance of optimal oral health for physical, mental and social well-being. 2 With recent efforts to satisfy the basic needs of older people in South Korea, senior citizens now pursue a higher level of needs than previous generations. 3 Accordingly, with growing interest in oral heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In the study, the analysis on oral health outcome measures showed that in the CN and MCI groups, the O’Leary and Löe & Silness indices significantly decreased, and the salivary flow rate significantly increased. This finding is consistent with the findings of a previous study, which examined the effects of oral health education utilizing a workbook and a mobile app [ 22 ]. It is speculated that in the current study, the use of a workbook after oral health education helped participants experiencing short-term memory problem easily understand the materials, as they could recall the lessons learned during the session.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study, the analysis on oral health outcome measures showed that in the CN and MCI groups, the O’Leary and Löe & Silness indices significantly decreased, and the salivary flow rate significantly increased. This finding is consistent with the findings of a previous study, which examined the effects of oral health education utilizing a workbook and a mobile app [ 22 ]. It is speculated that in the current study, the use of a workbook after oral health education helped participants experiencing short-term memory problem easily understand the materials, as they could recall the lessons learned during the session.…”
Section: Discussionsupporting
confidence: 92%
“…The cognitive activities consisted of oral health education and a post-education workbook developed in a previous study [ 22 ]. For oral health education, oral disease and the prevention of oral disease were discussed for 30 min per session.…”
Section: Methodsmentioning
confidence: 99%
“…Control group (Group C) 39 patients Group P:13 Group S:13 Group C:13) ≥60 years, ≥20 teeth, with periodontal disease referred to hospital between April 2013 & Dec 2016 Tellez et al (2019) USA: Dental clinics [ 94 ] Examining treatment fidelity of an individual-based MI intervention 60 patients Age ≥ 55 years, attending dental clinics appointment Tellez et al (2020) USA: Attending the dental clinics [ 95 ] Efficacy of individualised ‘Motivational Interviewing’ approach to oral health education 180 patients Age ≥ 55 years, fluent in English, with scheduled dental appointment Ting et al (2019) Taiwan: Community [ 96 ] Effectiveness of an oral health educational programme 539 older adults Age ≥ 65 years, can perform oral function exercises Johansson et al (2020) Sweden: Nursing home [ 97 ] Feasibility of oral health coaching programme 33 staff (I: 24 and C: 9) and 46 residents (I: 30 and C: 16) Staff and all residents Konstantopoulou et al (2020) Greece: Nursing home [ 98 ] Design, implement, and evaluate oral health education program for nursing home caregivers 55 caregivers (I:28, and C:27) Caregivers Lee et al (2020) South Korea: Nursing home [ 99 ] Effectiveness of oral health care program 135 residents (45 per group) Age ≥ 65 years not received any dental care within 6 mos. Lee et al, (2020) South Korea: Community [ 100 ] Effects of oral health education programme utilising a workbook 120 older adults (I:40, 40 and C:40) Age ≥ 65 years, able to read Korean, able to walk/move Ho et al, (2021) The Netherlands: Community [ 101 ] Early recognition of decreased oral health status and establishing a need for interprofessional care 407 older adults and 50 healthcare professionals Community-dwelling frail older people Healthcare professionals from general practice, a dental practice, home care organization Ki et al, (2021) South Korea: Community [ 102 ] Effectiveness of oral health education using a mobile app (OHEMA) on oral health & SWAL-QoL...…”
Section: Resultsmentioning
confidence: 99%
“…The app consisted of oral health education videos on five themes and corresponding workbook activities. The oral health education themes were chosen based on a literature review and expert advice, and a workbook developed in a previous study 20 was implemented in the app to enable users to complete activities after watching the videos. Considering the physical ageing and cognitive decline among older adults, the duration of each session was set to 5‐10 minutes, and the user environment was designed to minimise touch.…”
Section: Methodsmentioning
confidence: 99%